EVALUASI KINERJA INSTALASI PENGOLAHAN AIR LIMBAH RSD MANGUSADA KABUPATEN BADUNG - Harmayani, Kadek Diana (Jurnal Ilmiah Teknik Sipil; Jurnal Ilmiah Teknik Sipil, Vol. 25, No. 1, Januari 2021, 2021)
The Mangusada Regional General Hospital (RSD) as a provider of health facilities certainly produces liquid waste in every operational activity. Wastewater in the Wastewater Treatment Installation ( WWTI ) RSD Mangusada contains Biological Oxygen Demand (BOD 5 ), Chemical Oxygen Demand (COD), Total Suspended Solid (TSS), ammonia, total coliform, Total Dissolved Solid (TDS), detergent, oil and fat. This study aims to evaluate the performance of the WWT I as well as to determine the content in the wastewater after being treated by the IPAL RSD Mangusada according to the reference quality standards of the Governor of Bali Regulation No.16 / 2016 and Regulation of the Minister of Environment and Forestry of the Republic of Indonesia Number: P.68/Menlhk/Setjen/Kum.1/8/2016. The wastewater treatment system at RSD Mangusada uses a biological system. The data used in the analysis are secondary data, namely the Bed Occupation Rate (BOR) data in June 2020, the total number of beds, the average discharge of outlets in June 2020 and parameters of the quality and quantity of wastewater in the inlet and outlet of WWT I from January 2020 to July 2020. Based on the results of testing the quality and quantity of wastewater at the WWTI of RSD Mangusada outlet, the content of waste water in the outlet of WWTI is in accordance with the regulatory standards for the reference quality standards. In addition, the effectiveness of the efficiency of the WWT I at RSD Mangusada succeeded in reducing the ammonia content of 92.35%, BOD 5 64.03%, COD 63.97%, TSS 67.03%, oil and fat 64.64%, total coliform 76.84%. , and detergent at 76.25%. But the efficiency of the WWTI of RSD Mangusada was not good enough in reducing the TDS content of -3.92%.